Girls under pressure - Wilson, Jacqueline (London : London, 2007)
Ellie learns to deal with her self-image as she battles anorexia.
First published: Great Britain : Doubleday, 1998.
5.2
5-8.
5-8
Keywords: Anorexia nervosa -- Fiction; Weight control -- Fiction; Anorexia nervosa -- Fiction; Weight control -- Fiction